Pengaruh PDRB, PAD, dana berimbang, SiLPA terhadap belanja modal pada Kabupaten/Kota Provinsi Sumatera Utara Tahun 2013-2017 - Erniwati Telaumbanua, Neta; Doloksaribu, Megawati; Debora Sirait, Cici; Nelsari Malau, Yois (Jurnal Paradigma Ekonomika, 2021)
The purpose of this presentation is to determine the effect of calculating regional domestic income, local revenue, balancing funds, and excess budget on the Special Capital Expenditure of the Regency / City of North Sumatra Province in 2013-2017. This presentation uses a descriptive quantitative presentation type. The number of samples is 28 districts/cities. The sample selection is done by using purposive sampling. how to collect data with documentation techniques, and taken from secondary data. The data were tested by statistical data analysis in the form of multiple linear regression analysis where the classical assumption test was carried out first using SPSS. The value of Adjusted R square is 0.571, meaning that 57.1% of the capital expenditure variable can be applied by independent variables and the remaining 42.9% can be applied by variables that have not been made in this study.Â  Â